2019
DOI: 10.1016/j.tranon.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Immunostaining of HMGA2, LRP1B, and TP63 as Potential Biomarkers for Triaging Human Papillomavirus-Positive Women

Abstract: Background: Since human papillomavirus (HPV) DNA testing has been promoted as primary screening strategy, the triage method has also evolved from morphological testing to a molecular biomarker detection to improve screening efficiency. In this study, we investigated the performance of three HPV integration hot-spots, HMGA2, LRP1B, and TP63, as potential triage markers in HPV screening tests. Materials and Methods: This cross-sectional study was conducted from November 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…LRP1B was also detected as an HPV integration hotspot in CC [27], as suggested by our results, HPV-LRP1B integration was associated with the downregulation of LRP1B. Additionally, the LRP1B IHC staining score could serve as a sensitive biomarker for cervical lesion detection, with 0.801 area under curve (AUC), 90% sensitivity, and 56.76% specificity [39]. In our results, the expression status of LRP1B was identified as a biomarker for normal and neoplasm samples of CC and HNSCC, with AUC 0.8007 in HNSCC and 0.9024 in CC, which suggested that LRP1B could serve as a biomarker in CC and HNSCC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…LRP1B was also detected as an HPV integration hotspot in CC [27], as suggested by our results, HPV-LRP1B integration was associated with the downregulation of LRP1B. Additionally, the LRP1B IHC staining score could serve as a sensitive biomarker for cervical lesion detection, with 0.801 area under curve (AUC), 90% sensitivity, and 56.76% specificity [39]. In our results, the expression status of LRP1B was identified as a biomarker for normal and neoplasm samples of CC and HNSCC, with AUC 0.8007 in HNSCC and 0.9024 in CC, which suggested that LRP1B could serve as a biomarker in CC and HNSCC.…”
Section: Discussionsupporting
confidence: 67%
“…(B) E6 (total/spliced/un-spliced) expression in HPV 16 integration samples and HPV non-integration samples. (C) Distribution of HPV-LRP1B integration samples in a cervical carcinoma cohort [39]. (D) IHC staining score of LRP1B in cervical carcinoma samples with different integration sites or normal samples from the same cohort [39].…”
Section: Figure 2 Hpv Integration Status Was Associated With Increased E6 Expression and Reduced Lrp1b Expression (A) E6mentioning
confidence: 99%
“…The significantly increased gene expression of HMGA2 and TP63 has been reported in neoplastic samples where HPV is integrated into their introns, whereas LRP1B is under expression with HPV integration in their flanking region ( Michael et al, 2014 ; Hu et al, 2015 ). Therefore, a combination of HMGA2, LRP1B , and TP63 as potential biomarkers may be useful for screening during triage of HPV-positive patients, particularly for detecting CIN2+ ( Jiang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… Ibragimova et al (2018) and Koneva et al (2018) discovered that patients with integrated HPV status have a worse survival rate compared to those with episomal HPV. The increasing number of studies about HPV integration has stimulated the idea that HPV integration status may be a biomarker for the diagnosis, progression, and survival prediction, and even as a biomarker for cancer screening ( Han et al, 2015 ; Liu et al, 2018 ; Grayson et al, 2019 ; Jiang et al, 2019 ). Harlé et al (2019) found the same integration sites and DNA deletion regions between tongue and anal cancer of the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…The architectural transcription factor HMGA2 is a nonhistone DNAbinding factor that tightly binds to adenine and thymine (AT)-rich sequences in the minor groove of the DNA helix. 19 Jiang et al 20 identified that HMGA2 combined with LRP1B and TP63 function as potential biomarkers that are useful for triaging HPV-positive patients, especially CIN2+ patients. Notably, the depletion of HMGA2 counteracted the epithelial-mesenchymal transition and lymph node metastasis by suppressing the attenuated total reflectance (ATR)/Chk1 signaling pathway in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%